Molecular Phylogeny and Biogeographic Diversification of Linnaeoideae (Caprifoliaceae s. l.) Disjunctly Distributed in Eurasia, North America and Mexico - Wang, Hua-Feng; Landrein, Sven; Dong, Wen-Pan; Nie, Ze-Long; Kondo, Katsuhiko; Funamoto, Tsuneo; Wen, Jun; Zhou, Shi-Liang (2015)
Linnaeoideae is a small subfamily of erect or creeping shrubs to small trees in Caprifoliaceae that exhibits a wide disjunct distribution in Eurasia, North America and Mexico. Most taxa of the subfamily occur in eastern Asia and Mexico but the monospecific genus Linnaea has a circumboreal to north temperate distribution. In this study, we conducted phylogenetic and biogeographic analyses for Linnaeoideae and its close relatives based on sequences of the nuclear ribosomal ITS and nine plastid (rbcL, trnS-G, matK, trnL-F, ndhA, trnD-psbM, petB-D, trnL-rpl32 and trnH-psbA) markers. Our results support that Linnaeoideae is monophyletic, consisting of four eastern Asian lineages (Abelia, Diabelia, Dipelta and Kolkwitzia), the Mexican Vesalea, and Linnaea. The Mexican Vesalea was formerly placed in Abelia, but it did not form a clade with the eastern Asian Abelia; instead Vesalea and Linnaea are sisters. The divergence time between the eastern Asian lineages and the Mexican Vesalea plus the Linnaea clade was dated to be 50.86 Ma, with a 95% highest posterior density of 42.8 Ma (middle Eocene) to 60.19 Ma (early Paleocene) using the Bayesian relaxed clock estimation. Reconstructed ancestral areas indicated that the common ancestor of Linnaea plus Vesalea may have been widespread in eastern Asia and Mexico or originated in eastern Asia during the Eocene and likely migrated across continents in the Northern Hemisphere via the North Atlantic Land Bridges or the Bering Land Bridge. The Qinling Mountains of eastern Asia are the modern-day center of diversity of Kolkwitzia-DipeltaDiabelia clade. The Diabeliaclade became highly diversified in Japan and eastern China. Populations of Diabelia serrata in Japan and eastern China were found to be genetically identical in this study, suggesting a recent disjunction across the East China Sea, following the last glacial event.